Facile Fabrication of Binder-free Metallic Tin Nanoparticle/Carbon Nanofiber Hybrid Electrodes for Lithium-ion Batteries. (20th January 2015) - Wang, Jia; Song, Wei-Li; Wang, Zhenyu; Fan, Li-Zhen; Zhang, Yuefei
Abstract: In this work, a Sn nanoparticle (NP)/carbon nanofiber (CNF) hybrid with unique structure has been designed and fabricated via electrospinning and subsequent heat treatment. The cell assembled by the binder-free Sn NP/CNF hybrid demonstrates an effective capacity (46 mAh g −1 at 200 mA g −1 after 200 cycles) with high coulombic efficiency (up to 99.8%), suggesting a facile strategy for the scalable fabrication of electrochemically stable electrodes for LIBs. For understanding the electrochemical behaviors of the metallic Sn and carbon nanofibers in the lithiation/delithiation process, in situ transmission electron microscopy was applied to study the single hybrid structure. In the first charge/discharge process, real-time size variation of the Sn NP and CNFs was mainly focused, suggesting a two-step lithiation process in the metallic Sn NP. Structural characterization also indicates an irreversible delithiation in a single Sn NP/CNF hybrid structure. The electrochemical performance based on influence of carbonization temperature has also been discussed. The results and fundamental understanding of the lithiation/delithiation in the Sn-based hybrid anodes enables the communities to design flexible high-performance electrodes based on metallic active materials in a rational way.